Relationships between MMP-2, MMP-9, and ADAMDEC1 serum and tissue levels in patients with colorectal cancer - Zahra Mozooni; Kiana Khajeh Amiri; Nafiseh Golestani; Alireza Shahmohammadi; Sara Minaeian; Leyla Bahadorizadeh (Annals of Coloproctology)
Purpose Colorectal cancer (CRC) is the most common malignancy of the gastrointestinal system globally. Identifying specific gene expression patterns indicative of early-stage CRC could enable early diagnosis and rapid treatment initiation. Matrix metalloproteinases (MMPs) play crucial roles in extracellular matrix degradation and tissue remodeling. Among them, MMP-2 and MMP-9 have been found to be upregulated in various cancers, including CRC, and are associated with tumor invasion, metastasis, and angiogenesis. In contrast, a disintegrin and metalloproteinase like decysin 1 (ADAMDEC1) is a relatively newly discovered gene with demonstrated involvement in immune response and inflammation. This study investigated serum levels of MMP-2 and MMP-9, along with tissue expression of MMP-2, MMP-9, and ADAMDEC1, and explored potential associations with pathological and clinical factors in patients with CRC. Methods This study included 100 patients with CRC and 100 control participants. Tissue and blood samples were collected. Serum MMP-2 and MMP-9 levels were analyzed using the enzyme-linked immunosorbent assay. Quantitative real-time polymerase chain reaction was employed to assess the expression levels of MMP-2, MMP-9, and ADAMDEC1 in CRC tissue samples compared to adjacent control tissue. Results The expression levels of MMP-2, MMP-9, and ADAMDEC1 were significantly upregulated in CRC relative to adjacent control tissues. Analysis of clinicopathological features revealed statistically significant differences in the expression levels of MMP-2, MMP-9, and ADAMDEC1 between patients with CRC with and without lymphovascular invasion (P<0.001). Based on receiver operating characteristic curve analysis, these genes represent promising candidate diagnostic biomarkers for CRC. Conclusion MMP-2, MMP-9, and ADAMDEC1 levels may serve as potential diagnostic biomarkers for CRC.